2009
DOI: 10.1177/0269216309346540
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report of the integration of a palliative care team into an intensive care unit

Abstract: Nearly half of Americans who die in hospitals spend time in the intensive care unit (ICU) in the last 3 days of life. Minority patients who die in the ICU are less likely to formalize advance directives and surviving family members report lower satisfaction with the provision of information and sensitivity to their cultural traditions at the end-of-life. This is a descriptive report of a convenience sample of 157 consecutive patients served by a palliative care team which was integrated into the operations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 39 publications
(39 reference statements)
5
119
1
4
Order By: Relevance
“…This may be due to recent patientcentered practice changes in ICU settings, 22,58,59 including permitting longer and more frequent family presence. Transfer to other settings may be advisable in fewer cases, as it may move the patient away from providers who know them well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to recent patientcentered practice changes in ICU settings, 22,58,59 including permitting longer and more frequent family presence. Transfer to other settings may be advisable in fewer cases, as it may move the patient away from providers who know them well.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] During this time, palliative care treatment plans can be implemented, in place of or in addition to existing care plans, to reduce suffering and improve end-of-life care. 12,19,20 Despite the benefits of palliative care [18][19][20][21][22][23][24][25] and its growth in recent years, 20,25,27 it is not always available for inpatients, partly because the subspecialty palliative care workforce is not currently sufficient to reach all patients dying in hospital settings and partly because practitioners do not recognize shifts in patient trajectory indicating the need for palliative care consultation. [26][27][28][29][30][31][32] In an environment focusing on "cure," transition away from disease-modifying treatments to symptom control can seem counterintuitive.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previously published PC screening tools, this one should not require a provider to perform an additional patient interview, nor should it require a PC specialist or case manager for completion. 15,69,70,72 Ultimately, for this screening tool to increase rates of PC consultation as well as decrease the long latency between hospital admission and PC consultation, the results of the screening tool must be put to use. Multiple interventions based on this screening tool are conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…Many high-quality studies, including several randomized trials, [6][7][8] have examined the benefits of PC and shown it leads to significant improvements in patient quality of life and mood, 9 increased patient and caregiver satisfaction, 3,10,11 reduction in health care costs, [12][13][14] decreased intensive care unit (ICU) days, [15][16][17][18] hospital length of stay, physical symptomatology, and improved resource usage. 19 Despite the clear benefits of PC, the vast majority of patients who could benefit from PC are never identified or referred at any point during the course of their illness.…”
mentioning
confidence: 99%
“…So waren beinahe 50 % der Menschen, die in den USA im Krankenhaus verstarben, in ihren letzten 3 Tagen auf einer Intensivstation [9]. Die zunehmenden intensivmedizinischen Möglichkeiten durch Einsatz neuer apparativer, interventioneller, chirurgischerund medikamentöserMaßnah-men haben einen großen Fortschritt ge- …”
Section: Diskussionunclassified